Comparative proteome profiling of seminal components reveal impaired immune cell signalling as paternal contributors in recurrent pregnancy loss patients. (1st September 2022) - Jena, Soumya Ranjan; Nayak, Jasmine; Kumar, Sugandh; Kar, Sujata; Samanta, Luna
Abstract: Problem: Recurrent pregnancy loss (RPL) is usually evaluated from a women's perspective, however, recent evidence implies involvement of male factors as paternally expressed genes predominate placenta. During fertilization, prior to implantation the immune system purposefully produces early pregnancy factors with potent immunomodulatory properties for adaptation to antigenically dissimilar embryo. Therefore, it is hypothesized that paternal immunological factors play a role in RPL. Method of study: Comparative proteome profiling (label free liquid chromatography mass spectroscopy: LC‐MS/MS) of the seminal extracellular vesicles (SEVs), extracellular vesicle free seminal plasma (EVF‐SP) and spermatozoa was carried out in semen of RPL patients (n = 21) and fertile donors (n = 21). This was followed by pathway and protein‐protein interaction analysis, and validation of key proteins' expression (western blot). Results: A total of 68, 28 and 49 differentially expressed proteins in SEVs, EVF‐SP and spermatozoa of RPL patients, respectively, were found to be involved in inflammatory response, immune cell signalling and apoptosis. In SEVs, underexpressed GDF‐15 and overexpressed C3 imply distorted maternal immune response to paternal antigens leading to impaired decidualization. Dysregulated TGFβ signalling in EVF‐SP surmises defective modulation of inflammatory response and induction of immune tolerance to seminal antigens in the female reproductive tract through generation of regulatory T cells. Retained histone variants in spermatozoa construe defective expression of early paternal genes, while underexpressed PTN may inflict defective angiogenesis resulting in expulsion of decidua. Conclusions: Impaired modulation of immune response and improper placental development due to altered cytokine levels in seminal components may be the contributing paternal factors in RPL.